Thinking Outside the Block: External Focus of Attention Improves Reaction Times and Movement Preparation Times in Collegiate Track Sprinters - Attila J. Kovacs; Garrett F. Miles; Harsimran S. Baweja (MDPI AG, 2018)
While focusing attention on external cues (EF) has been shown to enhance performance track and field coaches tend to provide instructions that promote internal focus of attention (IF) during block starts. The aims of this study were to determine: (1) whether promoting EF versus IF would improve reaction time (RT) of sprinters, and (2) if changes occur at the level of central processes during movement preparation (premotor RT) or peripheral processes during movement execution (motor RT). Twelve collegiate track sprinters (age 20.8 ± 1.7) completed three testing sessions under EF, IF, and no focus instruction (NF) conditions. RT was recorded from the left and right blocks. Muscle activation time (EMG) was recorded from the vastus lateralis and gastrocnemius muscles. Mean rear foot RT was significantly shorter (p < 0.0001) under the EF (212.11 ms) compared with the IF (234.21 ms) and NF conditions (236.87 ms). Front foot RT was significantly shorter (p < 0.05) during EF (250.24 ms), compared to IF (266.98 ms) but not shorter than the NF (268.73 ms) condition. Mean premotor RT under the EF condition (157.75 ms) was significantly shorter (p < 0.001) compared with the IF (181.90 ms) and NF (173.60 ms) conditions. No differences were found in motor RT across conditions (p > 0.05). Adopting an EF improves RT during sprint starts. This improvement likely originates from a shortening in movement preparation time, as opposed to a faster excitation contraction coupling of the muscle fibers. These findings could potentially contribute to the development of new coaching methods aimed at improving the starting technique of athletes.